THE PROVISION OF FREE LEGAL AID IN INDIA: : INTERNATIONAL HUMAN RIGHTS ASPECT AS WELL AS THE CONSTITUTIONAL PURVIEW - Trivedi, Chetan; Dogra, Disha; Tandon, Ankita; Kumar, Sunil (Revista Gênero e Interdisciplinaridade, 2022)
One of the basic human rights of an individual irrespective of their age, caste, colour, nationality or any other status, is to have access to justice. All other rights lose their purpose without access to justice. An individual may have all other rights, though, if they don’t have an authority that looks after those rights and they cannot get those rights enforced at the time of need, all the rights would be useless making arbitrary violation of rights prevalent. Though said like a simple statement, the word ‘justice’ in itself is a multi-faceted term and needs to be understood from various angles. One of the basic requirements of having access to justice and getting justice in times of need is that the citizens of the State must be legally aware. Also, ‘access to justice’ means that a person must have access to the means to plead justice. First of all, individuals need to completely know and understand their rights and duties. Furthermore, they must be able to present themselves in front of competent authorities whenever those rights are violated. For those who lack the resources to access justice, the State shall provide the means through which they can attain it. Thus, the concept of free legal aid has been evolved over the years. The United Nations too has repeatedly emphasised upon the State’s duty to make their citizens legally aware and to provide free legal services to the citizens who cannot afford it. In this research, the provision of free legal aid in India is thoroughly explored. The research highlights the International Human Rights aspect of Free Legal Aid and the provision of Free Legal Aid in the Indian constitution. Also, it gives an idea about who is entitled to free legal aid and the mode in which the goals put forth by the International Human Rights law is achieved in India.